Golongan mudamat rempit: suatu ekspresi sub budaya - Rokiah Ismail,; Muhamad Fuad Abdul Karim,; Zaidah Mustapha, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
The research discusses the activities and sub-culture of a Mat Rempit group (outlaw bikers) in Kuala Lumpur. The research problem focuses on the sub-cultural activities and social expressions of specific norms and values of the group not only through motorcycle racing but also through other related activities such as their involvement in music, motorcycle thefts and drugs. Forty-five youths in Kuala Lumpur aged between 17 and 26 were selected using the purposive sampling method, and 7 of them were chosen for in-depth interviews which were conducted from Januari until November 2007. The research aims to describe the Mat Rempit group activities and examine the specific elements existing within their sub-culture and the various social expressions of Mat Rempit group who were involved in using the social and physical spaces as well as the available opportunities to carry out their specific activities and sub-culture. The research shows that amidst the various social transformations that are taking place within the society today, the Mat Rempit sub-culture is a form of social reaction and collective solution of the youths to the conventional norms and values which are perceived to limit their social activities. Mat Rempit activities and sub-culture are indirectly the group’s expression of life experiences and, more often than not, their leisure activities are seen by the public as socially problematic